Recruitment, Training, and Roles of the Bilingual, Bicultural Navegantes: Developing a Specialized Workforce of Community Health Workers to Serve a Low-Income, Spanish-Speaking Population in Rhode Island - Meghan McCarthy; Meghan McCarthy; Katherine Barry; Katherine Barry; Cindy Estrada; Brenda Veliz; Damaris Rosales; Morgan Leonard; Anne S. De Groot; Anne S. De Groot; Anne S. De Groot (Frontiers in Public Health, 2021)
Clínica Esperanza/Hope Clinic (CEHC) employs Navegantes, who are specially-trained bilingual Community Health Workers (CHW), as key team members who improve the ability of the clinic to provide care for and improve the health status of a large population of uninsured Spanish-speaking patients in Providence, Rhode Island. Given the growing demand for CHWs at the clinic and in the broader healthcare sector in the state, CEHC developed the Advanced Navegante Training Program (ANTP). The ANTP prepares community members to become certified CHWs who are equipped to provide patient navigation and lifestyle coaching as well as professional medical interpretation services. The ANTP is developed and taught by CEHC Navegantes who themselves are bilingual and bicultural peers of trainees as well as the population that CEHC serves. Upon graduation, ANTP trainees have been able to attain higher-paying and fulfilling careers in a range of healthcare and other community settings. The ANTP offers a low-cost, community-based model for training CHWs who are uniquely prepared to promote health and well-being among medically underserved patients.